Biogas Energy - Abbasi, Tasneem; Tauseef, S.M.; Abbasi, S.A.; SpringerLink (Online service) (New York, NY : Springer New York, 2012)
SpringerBriefs
Foreword -- Preface -- Biogas and biogas energy: An introduction -- A brief history of anaerobic Digestion and 'Biogas' -- Biogas and global warming -- Low-rate and high-rate anaerobic reactors/digesters/fermenters -- Biogas capture from animal manure -- Biogas capture from wastewaters: The high-rate anaerobic digesters -- Biogas capture from solid waste -- Capture of biogas from landfills.
Keywords: Renewable energy sources; Environmental sciences; Energy; Renewable and Green Energy; Environment, general